Methods to isolate a large amount of generative cells, sperm cells and vegetative nuclei from tomato pollen for “omics” analysis - Lu, Yunlong; Wei, Liqin; Wang, Tai (Frontiers in Plant Science, 2015)
The development of sperm cells (SCs) from microspores involves a set of finely regulated molecular and cellular events and the coordination of these events. The mechanisms underlying these events and their interconnections remain a major challenge. Systems analysis of genome-wide molecular networks and functional modules with high-throughput “omics” approaches is crucial for understanding the mechanisms; however, this study is hindered because of the difficulty in isolating a large amount of cells of different types, especially generative cells (GCs), from the pollen. Here, we optimized the conditions of tomato pollen germination and pollen tube growth to allow for long-term growth of pollen tubes in vitro with SCs generated in the tube. Using this culture system, we developed methods for isolating GCs, SCs and vegetative cell nuclei (VN) from just-germinated tomato pollen grains and growing pollen tubes and their purification by Percoll density gradient centrifugation. The purity and viability of isolated GCs and SCs were confirmed by microscopy examination and fluorescein diacetate staining, respectively, and the integrity of VN was confirmed by propidium iodide staining. We could obtain about 1.5 million GCs and 2.0 million SCs each from 180 mg initiated pollen grains, and 10 million VN from 270 mg initiated pollen grains germinated in vitro in each experiment. These methods provide the necessary preconditions for systematic biology studies of SC development and differentiation in higher plants.